A Sanctuary of Sounds - Burckhardt, Andreas (punctum books, 2013)
A Sanctuary of Sounds is an aural rewriting of William Faulkner's novel Sanctuary (1931). A polyphonic object. A garden - assemblage of blooms, of affects, of sounds, of meaning. An invitation to rethink appropriation ethically, aesthetically, and epistemologically. The appropriation of a body of work, of a physical body, of an idea, of data. The history of knowledge and its production is enabled by the process of appropriation, by the differentiation of noise. What does it mean to sample data, not of finished artworks, but of noise itself, the environment? Being victimized by the crushing quality of noise is all too human. Art must become an acoustic ecology. Noticing the landscape of objects, the relationships, the environment itself, in order to compose the music of tomorrow. Let the song of vibrant matter sing itself. A Sanctuary of Sounds is a noise-totality. Noise - nothing but noise. Noise as the first object of metaphysics. Noise as the synchronic/diachronic mediator of production-processes and their reorganization in society. Utopia and dystopia at once. A Sanctuary of Sounds is a dialectical poem, it is noise against noise - raping a rape.